Morality of the Marital Act in the Light of the "Wednesday Catechesis" of John Paul II - Jucewicz, Antoni (Studia Warmińskie, 2019)
This article presents the morality of a marital act in the light of the teaching of John Paul II contained in the Wednesday Catechesis. The essay includes the following themes: the norm of the marriage act and its ethical and theological interpretation, the ethical norm of the marital act interpreted in the perspective of "body language", the natural regulation of conception and the virtue of abstinence, the Christian witness of spouses given in the power of the Holy Spirit and marital spirituality. In the light of the undertaken analyzes, the morality of the marital act is based on the recognition of the "dual function of the sign in conjugal love" and the "inseparable connection" of this dual function. John Paul II reinterprets the understanding of this norm with the category of "body language", in which the inner truth of a marital act includes the meaning of love and procreation. This analysis also indicates the value of the virtue of abstinence in married life and the spirituality and witness of life of Catholic spouses implementing the moral standards of conjugal communion with the power of the Holy Spirit.